ANALYSIS OF THE HEALTH LEVEL OF THE STATE SAVING BANK Tbk WITH THE RGEC METHOD APPROACH (RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNING, CAPITAL) - Wanuri Wanuri; Wachidah Fauzijanti; Cahyani Tunggal Sari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this study was to determine the assessment of the soundness of the State Savings Bank in terms of the RGEC method approach which includes risk profile, good corporate governance, earnings and capital factors. The research method used is a qualitative descriptive method carried out through a literature study that examines (especially) secondary data in the form of governance reports & Bank BTN financial reports, laws and regulations. The results of the analysis of the Bank's Health Level, the Risk Profile factor gets a composite rating of 2. While the assessment of liquidity risk using the LDR ratio can be said to be "Sufficiently Healthy" with a composite rating of 3. Meanwhile in 2019 the LDR is categorized as less healthy with a composite rating of 4. The assessment factor for Good Corporate Governance with a self-assessment rating is good category with a composite rating of 2. The Earnings factor with an assessment using ROA can be said to be quite healthy, while the 2019 period includes the criteria for being less healthy. The Capital Factor with an assessment using CAR ratio is said to be very healthy by getting a rating of 1.